Develop and Validate Intubation Checklist for Critically Ill Patients Admitted in Intensive Care Units of the Teaching Hospital of Navi Mumbai - Mankayarkarasi, S.; Preethi Mathew, Maria; Sinha, Sagar (International Journal of Nursing Research, 2023)
Aims: This study aims to develop and validate intubation checklist for critically ill patients admitted in intensive care units of the teaching hospital of Navi Mumbai. Materials and Methods: Expert data for an intubation checklist for critically ill patients are gathered using the Delphi method. The Delphi method is a structured communication technique or method that uses a panel of experts to make decisions. In three rounds, the experts respond. A facilitator or change agent summarizes the experts’ predictions and the reasons they gave for their predictions after each round. Experts are thus encouraged to revise previous responses in light of the responses of other panelists. Results: The findings show that agreement for development intubation has increased. One hundred percent of the 15 experts strongly agreed. Endotracheal intubation complications are reduced by 86.7% when using the endotracheal intubation checklist. The content of this endotracheal intubation checklist is appropriate in 80% of cases. The checklist for endotracheal intubation is superior to the protocol. Conclusion: A critically ill patient intubation checklist was created and validated. In total, 42 items were suggested by experts. In rounds two and three, the expert consensus was accepted, and the majority of items in both rounds had no significant differences in opinion. ItemContent Validity Index (CVI) (below 0.78) and slightly different opinions were removed. The final checklist included 41 items with 100% expert agreement, a high CVI-I of ranking agreement, and an inter-rater reliability of 0.94, indicating that the tool is highly valid and reliable.